AN INFLUENCE OF UNIAXIAL STRAIN (PRESSURE) ON THE TEMPERATURE OF THE BOSE-EINSTEIN CONDENSATION OF INTERSITE BIPOLARONS: POSSIBLE IMPLEMENTATION FOR RBa2Cu3O7-δ CUPRATES - Jalekeshov, A.S.; Ya.Yavidov, B. (SCIENCE and SOCIETY, 2021)
A universal approach is proposed to study the influence of strain (pressure) on the temperature of Bose-Einstein condensation of intersite bipolarons within the extended Holstein model. It is shown that uniaxial strain (pressure) derivatives of the temperature of such a Bose-Einstein condensation strongly depend on the arrangement of ions in the lattice. In particular, they may be positive or negative. A connection between the theoretically obtained results, along with the experimental data, on the influence of uniaxial pressure (strain) on Tc of RBa2Cu3O7-δ family cuprates is discussed.